Mapping the Landscape of Internet Pornography, Loneliness, and Social Media Addiction: A CiteSpace Bibliometric Analysis. - Prasad, Abhishek; Subramanian, Kadhiravan (International Journal of Mental Health & Addiction, 2025)
A comprehensive bibliometric analysis using CiteSpace explores global scientific research trends concerning internet pornography, loneliness, and social media addiction from 1993 to 2023. The study reveals disciplinary distributions, evolving patterns, influential scholars, and contributing institutions. Notably, the United States accounts for over 29% of publications, with Griffiths MD and Beutel ME emerging as leading contributors with 22.7% and 18.2% respectively. A remarkable 2750% surge in scholarly publications from 2020 to 2023 underscores increasing interest in the subject. Keyword analysis identifies emerging trends and focal points, with terms such as "acquired immunodeficiency syndrome," "pornography use," and "addiction" showing significant citation activity. Leading institutions include New York University and University College London. Key metrics like sigma value (0.98), centrality (1.00), and citation burstness (32) provide valuable insights into the importance and influence of identified clusters within the academic landscape. This analysis sheds light on scholarly discussions, aiding in the comprehension of internet pornography, loneliness, and social media addiction.